2016
DOI: 10.1177/1535370215622708
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TUG1 acts as a tumor suppressor in human glioma by promoting cell apoptosis

Abstract: Previous studies have revealed multiple functional roles of long non-coding RNA taurine upregulated gene 1 in different types of malignant tumors, except for human glioma. Here, it was designed to study the potential function of taurine upregulated gene 1 in glioma pathogenesis focusing on its regulation on cell apoptosis. The expression of taurine upregulated gene 1 in glioma tissues was detected by quantitative RT-PCR and compared with that in adjacent normal tissues. Further correlation analysis was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
154
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(161 citation statements)
references
References 22 publications
6
154
1
Order By: Relevance
“…However, Zhang et al [10] found that TUG1 was generally downregulated in NSCLC, and low TUG1 expression was associated with advanced TNM stage, larger tumor size, as well as poorer OS. In a most recent study [16], Li et al found that TUG1 functions as a tumor suppressor in glioma by activating caspase-3 and caspase-9-mediated intrinsic pathways and inhibiting Bcl-2-mediated anti-apoptotic pathways. These findings indicate that the expression pattern of lncRNAs may feature higher tissue specificity in comparison with that of protein-coding genes [23,24].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, Zhang et al [10] found that TUG1 was generally downregulated in NSCLC, and low TUG1 expression was associated with advanced TNM stage, larger tumor size, as well as poorer OS. In a most recent study [16], Li et al found that TUG1 functions as a tumor suppressor in glioma by activating caspase-3 and caspase-9-mediated intrinsic pathways and inhibiting Bcl-2-mediated anti-apoptotic pathways. These findings indicate that the expression pattern of lncRNAs may feature higher tissue specificity in comparison with that of protein-coding genes [23,24].…”
Section: Discussionmentioning
confidence: 98%
“…TUG1 was recently confirmed to be upregulated in colorectal cancer [10], hepatocellular carcinoma [13], urothelial carcinoma of the bladder [14], and osteosarcoma [15] and thus facilitates the proliferation of tumor cells. By contrast, TUG1 expression has been reported to be downregulated in non-small cell lung cancer (NSCLC) and glioma [16,17], and thus, it may function as a tumor suppressor in some types of cancer. However, the expression pattern and function of TUG1 in ESCC have rarely been reported.…”
mentioning
confidence: 87%
“…LncRNA taurine upregulated gene 1 ( TUG1 ) was initially identified as an essential gene for retinal development in the developing mouse eye [8]. Subsequent research revealed that TUG1 was abnormally regulated in tumorigenesis, either as a potential tumor suppressor or as an oncogene [910]. However, the role of TUG1 in breast cancer is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, radiotherapy treatment for spinal cord glioma is associated with worsened outcomes [6]. Interestingly, one study provides new insight for understanding the function of the long non-coding RNA taurine up-regulated gene 1 (lncRNA TUG1) in cancer biology, with the potential of TUG1 overexpression in glioma therapy [7].…”
Section: Introductionmentioning
confidence: 99%